2013
DOI: 10.1371/journal.pone.0066348
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Ultrasonic Detection of Polyurea Crosslinked Silica Aerogel Implants

Abstract: BackgroundPolyurea crosslinked silica aerogels are highly porous, lightweight, and mechanically strong materials with great potential for in vivo applications. Recent in vivo and in vitro studies have demonstrated the biocompatibility of this type of aerogel. The highly porous nature of aerogels allows for exceptional thermal, electric, and acoustic insulating capabilities that can be taken advantage of for non-invasive external imaging techniques. Sound-based detection of implants is a low cost, non-invasive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…61 through series of in-vitro [44,198] and in-vivo [42,43] analysis. However, more works are still required for aerogels with various formulations to be applied in biological systems.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…61 through series of in-vitro [44,198] and in-vivo [42,43] analysis. However, more works are still required for aerogels with various formulations to be applied in biological systems.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ability to image an implant located in the peripheral region of the body with minimum hurts to the patient is an important part of designing of implant based biomaterial [42]. The acoustic absorption of aerogels has been recently considered for non-invasive and rapid imaging of aerogel-based implants located in the peripheral region of the body, especially in peripheral nervous system.…”
Section: Aerogel For Biomedical Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Crosslinked silica aerogels have been investigated recently for biocompatibility and their potential to serve as a nerve growth scaffold [10][11][12][13]. A recent in vivo ultrasound study of crosslinked silica aerogels [14] demonstrated a detectable and unique acoustic response compared to the surrounding tissue. Other non-invasive imaging modalities such as X-ray imaging can provide valuable information about material properties and have not been investigated for crosslinked silica aerogels to date.…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of phosphor-based thermometry is that temperature-dependent luminescence can be measured from a distance and even through intervening scattering or partially absorbing media [6]. Elastomers from the family of polydimethylsiloxane (PDMS) are flexible and inert polymers with tunable chemical, physical, and electrical properties used in some cases for biomedical and in vivo applications [7]. The ability to ''dope'' these polymers creates a unique and versatile ''carrier'' for active materials such as phosphor particles routinely used in phosphor thermography [8].…”
Section: Introductionmentioning
confidence: 99%